ANALISIS KINERJA PEGAWAI PADA KANTOR CAMAT KECAMATAN LIMUN KABUPATEN SAROLANGUN - Fitri, Hazalia (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2015)
The purpose of this study is to improve the performance of employees at the sub-district office of Limun District, Sarolangun Regency through 5 main factors. The performance of the five factors is used, namely: Quality, Quantity of Cooperation, Accuracy, and Creativity where Quality: is the degree to which the results of implementing activities are close to perfection or close to the goal what is expected by the company Quantity: is the achievement of work targets in their fields that produce the amount of rupiah, the number of units, the number of activity cycles completed. Collaboration: is the degree to which an employee can carry out a job function with the abilities of the employee so that they can establish good relationships between fellow employees and their superiors. Accuracy: is the degree to which an activity is completed at the desired time by showing the coordination of the output of other people and the time available for other activities or in other words, determination is the effectiveness and efficiency of work on employees. And Creativity: is the degree to which the use of human resources or the ability of employees to create many innovations or new things in completing a job. The analysis used in the performance improvement strategy is qualitative analysis. The data used are primary and secondary data. Data collection procedures were carried out by means of questionnaires, observations and interviews.